Germany's Bundesliga : does money score goals? - Schmedders, Karl; Snyder, Charlotte; Tinz, Sophie ([London] : SAGE, 2016)
During one of the most nerve-wracking football matches of the 2012-2013 Bundesliga season, life-long friends Franz Dully and Max Vogel begin arguing about whether the wealth of a football club determines its success during the season. In order to disprove Vogel's claim that 'money scores goals,' Dully must analyze the Bundesliga's current market values, points earned, and mid-season leader data.
Originally Published in: Schmedders, K., Snyder, C., & Tinz, S. (2013). Germany's Bundesliga: Does Money Score Goals? (case revised 19/03/2014). 5-113-002. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Fussball-Bundesliga.; Soccer -- Germany -- Management -- Case studies; Soccer -- Economic aspects -- Germany -- Case studies